Impact of the COVID-19 pandemic on emergency and elective hip surgeries in Norway - Magnusson, Karin; Helgeland, Jon; Grøsland, Mari; Telle, Kjetil (Acta Orthopaedica, 2021)
Background and purpose — Many countries implemented strict lockdown policies to control the COVID-19 pandemic during March 2020. The impacts of lockdown policies on joint surgeries are unknown. Therefore, we assessed the effects of COVID-19 pandemic lockdown restrictions on the number of emergency and elective hip joint surgeries, and explored whether these procedures are more/less affected by lockdown restrictions than other hospital care. Patients and methods — In 1,344,355 persons aged ≥ 35 years in the Norwegian emergency preparedness (BEREDT C19) register, we studied the daily number of persons having (1) emergency surgeries due to hip fractures, and (2) electively planned surgeries due to hip osteoarthritis before and after COVID-19 lockdown restrictions were implemented nationally on March 13, 2020, for different age and sex groups. Incidence rate ratios (IRR) reflect the after-lockdown number of surgeries divided by the beforelockdown number of surgeries. Results — After-lockdown elective hip surgeries comprised one-third the number of before-lockdown (IRR ~0.3), which is a greater drop than that seen in all-cause elective hospital care (IRR ~0.6). Men aged 35–69 had half the number of emergency hip fracture surgeries (IRR ~0.6), whereas women aged ≥ 70 had the same number of emergency hip fracture surgeries after lockdown (IRR ~1). Only women aged 35–69 and men aged ≥ 70 had emergency hip fracture surgery rates after lockdown comparable to what may be expected based on analyses of all-cause acute care (IRR ~0.80) Interpretation — It is important to note for future pandemics management that lockdown restrictions may impact more on scheduled joint surgery than other scheduled hospital care. Lockdown may also impact the number of emergency joint surgeries for men aged ≥ 35 but not those for women aged ≥ 70.